High Hydrostatic Pressure–A Key Element to Investigate Molecular Dynamics in Biosystems - Peters, Judith (Frontiers in Physics, 2022)
Temperature variations are often used to investigate molecular dynamics through neutron scattering in biosystems, as the techniques required for that are well-known. Hydrostatic pressure is much less applied due to technological difficulties. However, within the last decade, a reliable and suitable equipment was developed at the Institut Laue Langevin, Grenoble, France, which is available on different instruments. Here, an overview is given how it can be employed in relation with elastic incoherent neutron scattering to study, for instance, the impact of transitions on atomic mobility in biological samples and which conclusions can be drawn.